Effects of S-1-propenylcysteine, a sulfur compound in aged garlic extract, on blood pressure and peripheral circulation in spontaneously hypertensive rats. (30th January 2018) - Ushijima, Mitsuyasu; Takashima, Miyuki; Kunimura, Kayo; Kodera, Yukihiro; Morihara, Naoaki; Tamura, Koichi
Abstract: Objectives: This study was designed to investigate the antihypertensive effect of S -1-propenylcysteine, a characteristic sulfur compound in aged garlic extract, using a hypertensive rat model. Methods: The blood pressure and tail blood flow of both spontaneously hypertensive rats and control Wistar Kyoto rats were measured by the tail-cuff method and the noncontact laser Doppler method, respectively, at various times after single oral administration of a test compound for 24 h. Key findings: Treatment with S -1-propenylcysteine (6.5 mg/kg BW) significantly decreased the systolic blood pressure of spontaneously hypertensive rat approximately 10% at 3 h after administration, and thereafter, the systolic blood pressure gradually returned to the baseline level in 24 h. The effect of S -1-propenylcysteine was dose-dependent and was maximal at the dose of 6.5 mg/kg BW at 3 h. However, the other compounds such as S -allylcysteine and S -allylmercaptocysteine in aged garlic extract were ineffective. In addition, S -1-propenylcysteine had no effect on systolic blood pressure of control Wistar Kyoto rats. Furthermore, S -1-propenylcysteine significantly increased the blood flow at 3 h after administration at the dose of 6.5 mg/kg BW. Conclusions: S -1-propenylcysteine is a key constituent of aged garlic extract responsible for its antihypertensive effect, and the effect of S -1-propenylcysteine involves the improvement in peripheral circulation.